Spooky action at a distance : the phenomenon that reimagines space and time-- and what it means for black holes, the big bang, and theories of everything - Musser, George (Scientific American/Farrar, Straus and Giroux, 2015)
"A tour of modern physics that provocatively examines growing understandings about the near-fantastical impact of particles to affect each other across the vastness of space,"--Amazon.com.